Spatial and Temporal Effects of Decommissioning a Zinc Smelter on the Sediment Quality of an Estuary System: Sepetiba Bay, Rio de Janeiro, Brazil - Gonçalves,Rodrigo A. (2020)
Sepetiba Bay, Rio de Janeiro, Brazil, was home to a zinc smelter until its shutdown in 1998, and during 2011 the remains of the smelter were decommissioned. This study investigates the impact of decommissioning on metal concentrations in the bottom sediments of the bay. In addition to Zn and Cd, Cr, Cu, Ni and Pb are also quantified. The results show that over these 15 years, Cd and Zn concentrations have decreased by 100 and 70%, respectively. Temporal effects are also studied by applying five dated 210Pb cores, which are validated using the Zn and Cd profiles. The observed decrease in the Zn concentration in oysters is correlated with its reduction in the sediment. It was possible to verify the impact of Cr, Cu, Ni and Pb on the sediment quality due to the remaining metallurgical industries in the Sepetiba Bay basin.